Winds Howl Through the Mansions - Matur, Bejan (Book collections on Project MUSE., 2019)
Drawn from Hong Kong International Poetry Nights 2011, Winds Howl Through the Mansions is a chapbook of poetry by Bejan Matur, accompanied by English and Chinese translations. Winds Howl Through the Mansions is also available along with the works of other internationally renowned poets in Words and the World (Twenty-volume Set). Selected poems from this volume are featured in the anthology Words and the World: International Poetry Nights in Hong Kong